Exploring Grade 9 Physical Science teachers' views and experiences on the inclusion of indigenous knowledge in their lessons: a Namibian case study - Simasiku, Fredrick Simataa (Rhodes University, Faculty of Education, Department of Education, 2017)
There is extensive research on the fact that the learning of science is assisted through the inclusion of the prior everyday knowledge and local knowledge that learners bring from home and from within their communities. It is precisely for this reason that the Namibian Learner Centered Education (LCE) curriculum encourages teachers to include learners' prior everyday knowledge in their science lessons. However, the inclusion of traditional knowledge/local knowledge or indigenous knowledge (IK) and how this should be done has been largely ignored both in the Namibian school science curriculum and textbooks. It is against this background that this study sought to explore teachers' views and experiences on the inclusion of IK in Physical Science Grade 9 lessons as well as the pedagogical strategies that they use. This research used a mixed methods approach (quantitative and qualitative data were collected) which was underpinned by the interpretive paradigm. Within the interpretive paradigm, I employed a case study approach. The study was carried out in the Endola education circuit of the Ohangwena Region. Essentially, the study explored three things: Firstly, the views, experiences and pedagogical strategies of Grade 9 Physical Science teachers on the inclusion of indigenous knowledge in their lessons. Secondly, to find out what factors enable the teachers to integrate their local knowledge into Physical Science lessons? Thirdly, to look at constraints that affect Grade 9 Physical Science teachers in the use of local knowledge in their science lessons. Data were collected using questionnaires and semi-structured interviews. The data obtained were validated in two ways, firstly, the data were triangulated from different data gathering techniques, and secondly, validation was done by member checking of the transcribed scripts. To make meaning from the data generated, Vygotsky's (1978) socio-cultural theory was used as a lens to analyze the data. The data generated were coded inductively and presented in graphs, tables and descriptive texts to make meaning. The findings from the research revealed that teachers in the Endola circuit do make some efforts to include indigenous knowledge in their lessons. Furthermore, teachers seemed to grasp the benefits and constraints that come with the inclusion of indigenous knowledge in their science lessons. For example, it emerged that indigenous knowledge enables learners to link what they are taught in the science classroom to what is happening in the community or at home, thereby enhancing their understanding of the concepts. Topics such as acids and bases, friction, combustion, static electricity and pressure emerged as some of the topics in which teachers include indigenous knowledge. On the other hand, the issue of language, textbooks and lack of indigenous knowledge by teachers affects the way teachers are able to include IK in their lessons. This study thus recommends that teachers should explore different indigenous practices that can be linked to the topics in the curriculum or syllabus to enhance learning and teaching. Furthermore, they need to involve local communities that possess indigenous knowledge to help in delivering indigenous practices during the lessons. Lastly, teachers and communities should start developing learning and teaching support materials that are useful when local knowledge is included.
Keywords: Uncatalogued